Engaging Students with Art‐Based S‐R‐C (Sense of Belonging, Resistance, and Coalition Building) Strategies for Anti‐Racism. (5th February 2023) - Shin, Ryan; Lim, Maria; Hsieh, Kevin
Abstract: In this article, we discuss our struggles and efforts to respond to Asian American and Pacific Islander (AAPI) hate crimes and anti‐Asian racism, as well as explore ways to address the issues of anti‐Asian racism, violence, myths, and stereotypes in the art classroom. We researched and learned from contemporary Asian American artists, attended anti‐racism virtual talks, and examined various anti‐racism pedagogical approaches. As an outcome of our research to confront anti‐racism, we developed S‐R‐C strategies to engage students with art‐based anti‐racism, which include facilitating a sense of belonging (S), resisting anti‐Asian racism (R), and coalescing with other minority groups and allies (C). These strategies were developed to fully embrace the equity, diversity, and inclusivity of AAPI sequentially and holistically. This article also reports how we use the S‐R‐C strategies to guide our pre‐service art teachers to confront anti‐Asian racism and advocate for anti‐racism teaching practices.